2022
DOI: 10.1155/2022/2443615
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Active Compounds and Mechanisms of Angong Niuhuang Wan on Ischemic Stroke Based on Network Pharmacology and Molecular Docking

Abstract: Background and Purpose. Angong Niuhuang Wan (ANW) is a traditional Chinese herbal formula that has been widely used for the treatment of ischemic stroke, whereas its underlying therapeutic mechanism remains unclear. The objective of the study is to explore the main bioactive ingredients and interaction mechanism of ANW on ischemic stroke based on the network pharmacology method. Methods. The chemical ingredients of ANW were retrieved from TCMSP, TCMID, and literature. We predicted the potential targets of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Subsequently, the ligand molecularly docked to the receptors using AutoDock, and PyMOL software ( https://pymol.org/2/ ) was used for network visualization (Zhang et al. 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the ligand molecularly docked to the receptors using AutoDock, and PyMOL software ( https://pymol.org/2/ ) was used for network visualization (Zhang et al. 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Zhang et al. [ 133 ] used network pharmacology and molecular docking methods to study AGNHW, which identified quercetin, β-estradiol, berberine, baicalein and β-sitosterol as the main active ingredients and identified the key targets, including interleukin 6 (IL-6), AKT1, mitogen-activated protein kinase 3 (MAPK3), PIK3CA and tumor necrosis factor (TNF). Until now, the use of metabolomics to study the active ingredient of AGNHW and its application in ischemic stroke has not been reported.…”
Section: Metabolomics In the Treatment Of Is With Chmmentioning
confidence: 99%
“…The potential therapeutic target genes were ranked according to the degree value, and the targets and active ingredients with higher degree values were screened. [24] 2.4. Gene ontology and kyoto encyclopedia of genes and genomes analyses…”
Section: Construction and Analysis Of Protein-protein Interaction Net...mentioning
confidence: 99%